Pengembangan Video Pembelajaran Berbasis Kontekstual pada Materi Gaya Kelas IV Sekolah Dasar - Juwita Asmara; Irwan Koto (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This research aims to (a) create and develop contextually based animated video learning media for learning science on Gaya material. Learning media is created by combining text, images, animation, audio and video. (b) to measure the feasibility and practicality of contextual-based learning video media. at SDN 11 Central Bengkulu. This research is research and development using the Borg and Gall model. The research object is contextual-based learning video media. The research stage includes (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) use trials, (7) product revision. The data collection technique used was a validation questionnaire from material experts, language experts and presentation experts which were analyzed quantitatively descriptively. The research subjects were 18 grade IV students at SDN Bengkulu Tengah. The results of this research are contextual-based learning video media in science learning style material with material aspect feasibility of 0.81 high validity with very feasible criteria, language aspect feasibility of 0.75 high validity with appropriate criteria, and presentation aspect 0.80 high validity with criteria worthy. Practicality with a score of 79.38 with a percentage of 79.38% meets the practicality criteria. So, contextual-based learning video media in learning science material in Gaya is feasible and practical to use.